PENGARUH ESG DAN INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2023)
This study aims to examine the impact of ESG and Intellectual Capital on company performance. In selecting the samples, the method employed was purposive sampling technique, and there were 12 companies from the energy sector, basic material sector, and consumer non-cyclical sector listed on the Indonesia Stock Exchange during the period of 2017-2021. Data analysis was conducted using panel linear regression with Eviews 12 and the outcomes indicate that ESG and Intellectual Capital positively influence company performance. This study hoped to contribute reference data for companies in making decisions by considering ESG and intellectual capital, which can have an impact on company performance.